Risk Factors Associated with Treatment Default Among Tuberculosis Patients in Adamawa State, Nigeria - Charles Okoro; Olateju Alao Bamigbala; Ayodeji Oluwatobi Ojetunde; Abdulmudallib Ibrahim (Galician Medical Journal, 2022)
Background. Tuberculosis is an infectious disease caused by bacteria called Mycobacterium tuberculosis. The treatment of drug-resistant tuberculosis is complex, costly, and usually has poor outcomes. Treatment default is well known as a very significant factor associated with drug-resistant tuberculosis.